2013
DOI: 10.1371/journal.pone.0068138
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Different Ligands Induced Conformation Change of β2 Adrenergic Receptor-Gs Protein Complex

Abstract: β2 adrenergic receptor (β2AR) regulated many key physiological processes by activation of a heterotrimeric GTP binding protein (Gs protein). This process could be modulated by different types of ligands. But the details about this modulation process were still not depicted. Here, we performed molecular dynamics (MD) simulations on the structures of β2AR-Gs protein in complex with different types of ligands. The simulation results demonstrated that the agonist BI-167107 could form hydrogen bonds with Ser2035.42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…NMR spectroscopy has been reported to map three [ 142 ], and molecular dynamic simulations to map seven receptor activation states to different energy states [ 143 ]. Some ligands (‘true’ neutral antagonists) do not appear to shift the receptor activity level set by specific assay conditions [ 144 ]. Different types of ligands (agonists, antagonists, and inverse agonists) modulated the conformational dynamics differently [ 145 ].…”
Section: Molecular Mechanisms and Structural Basis Of Inverse Agonmentioning
confidence: 99%
“…NMR spectroscopy has been reported to map three [ 142 ], and molecular dynamic simulations to map seven receptor activation states to different energy states [ 143 ]. Some ligands (‘true’ neutral antagonists) do not appear to shift the receptor activity level set by specific assay conditions [ 144 ]. Different types of ligands (agonists, antagonists, and inverse agonists) modulated the conformational dynamics differently [ 145 ].…”
Section: Molecular Mechanisms and Structural Basis Of Inverse Agonmentioning
confidence: 99%
“…[15][16][17] MD simulations have shown that conformational dynamics of the GPCR-G protein complex depends on the bound ligands. 18,19 Moreover, MD simulations have suggested that the binding of the active GPCR is necessary for nucleotide release from the G protein. [20][21][22][23] However, due to limited timescales, conventional MD (cMD) simulations often suffer from insufficient sampling, precluding proper free energy calculations to characterize GPCR-G protein interactions quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between β 2 -AR and ligands, and the mechanism of receptor activation have been intensively studied (Bai et al 2013 ; Cherezov et al 2007 ; Rasmussen et al 2011a , b ; Ring et al 2013 ; Staus et al 2014 ; Kim et al 2013 ; Zocher et al 2012 ; Deupi et al 2012 ; Yao et al 2006 ). Analysis of the ligand-binding region of β 2 -AR on the basis of recently solved high-resolution crystal structures revealed several highly conserved amino acids that might be involved in ligand binding.…”
Section: Introductionmentioning
confidence: 99%